Negative Association Between Allopregnanolone and Cerebral Serotonin Transporter Binding in Healthy Women of Fertile Age - Sundström Poromaa, Inger; Comasco, Erika; Bäckström, Torbjörn; Bixo, Marie; Jensen, Peter; Frokjaer, Vibe G. (Frontiers in Psychology, 2019)
Allopregnanolone is a metabolite of the sex hormone progesterone, with suggested relevance for female mood disorders. While allopregnanolone and serotonin are known to influence psychological well-being, the molecular and psychological specifics of their relationship are to date poorly understood, especially in women of fertile age who experience regular fluctuations of progesterone across the menstrual cycle. Availability of serotonin in the synaptic cleft is regulated by the serotonin transporter (SERT), which can be imaged in the living human brain by use of positron emission tomography (PET) and the radiotracer [11C]DASB. To evaluate sex-specific allopregnanolone-SERT interactions, the present study investigated the relationship between cerebral SERT availability, serum allopregnanolone levels and psychological well-being in women of fertile age. Brain imaging data, self-reported symptoms of mental distress and emotion regulation, and biobank material from ninety healthy women were available from the Center for Integrated Molecular Brain Imaging (CIMBI) database. Age, BMI, and daylight minutes were included as covariates in the analyses and SERT genotype (5-HTTLPR) was considered a potential confounder. Lower serum allopregnanolone levels were associated with higher SERT binding in the prefrontal cortex. Moreover, allopregnanolone levels were negatively associated with measures of alertness, although this finding was not mediated by prefrontal cortex SERT binding. These findings suggest a link between the typical psychological well-being experienced in the follicular phase when allopregnanolone levels are low and higher SERT in the prefrontal cortex, a region for higher cognitive functions and top-down regulation of emotions.